ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2011 – 2016 ) - Waskito, Meindro; Hidayat, Dewi (Kinerja, 2020)
Abstract : The purpose of this research to determine the difference between the financial performance before and after the acquisition of a nonfinancial company listed on the Indonesia Stock Exchange using which is proxied with the ratio of finance current ratio, total assets turn over, return on equity, debt to equity ratio, earnings per share. The research period used is 2011-2016. The population in this study are companies that do acquisitions listed on the BEI. The sample selection of this research using non-probability sampling techniques, with purposive sampling approach. The sample size is 17 samples. The data used are secondary data. Tests conducted are the descriptive statistical test, normality test, and test wilcoxon signed-rank test. The data analysis used to test the hypothesis is by using a paired sample analysis differentiation technique. Based on the result of research indicate that there were significant differences in total assets turnover, return on equity, and earnings per share, while the current ratio and debt to equity ratio did not have a significant difference between before and after the acquisition.